3D-integrated metasurfaces for full-colour holography - Hu, Yueqiang; Luo, Xuhao; Chen, Yiqing; Liu, Qing; Li, Xin; Wang, Yasi; Liu, Na; Duan, Huigao (Light, 2019)
A compact optical device comprising vertically stacked metasurfaces can simultaneously generate microscopic text and full-colour holograms for encrypted data storage and colour displays. Metasurfaces are ultrathin, synthetic materials patterned with features smaller than the wavelength of light, enabling researchers to manipulate how light rays behave when they hit the surface. Huigao Duan and co-workers at Hunan University in Changsha, China and the University of Heidelberg in Germany fabricated a metasurface device that simultaneously generates full-colour holograms and microprint – tiny lettering - for use in encryption and security. Their design comprises stacked metasurfaces - one that generates colour microprint when illuminated with white light, and another that projects holograms in full colour under RGB lasers. The device can encrypt and store data more efficiently, and with lower levels of crosstalk, than previous designs.
Gesehen am 17.02.2020